The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1044/2019_jslhr-s-19-0121
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Response to Speech Production in Stuttering and Normally Fluent Preschool-Age Children

Abstract: Purpose We studied speech-related sympathetic nervous system arousal of preschool-age children who do (CWS) and do not stutter (CWNS) and its association with children's proclivity to experience negative emotions and children's self-reported attitudes toward speaking. Method Electrodermal activity measures were collected from 32 preschool-age children while they engaged in a picture description and a nonword repetition task. Children's proclivity to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…However, our findings with the other autonomic nervous system measures (SCL and RSA) corroborate the existing psychophysiological studies of preschool-age CWS. Specifically, a recent study from our laboratory (Tumanova and Backes, 2019) and the studies of others (Jones et al, 2014;Zengin-Bolatkale et al, 2015) reported no significant differences in baseline SCL between preschool-age CWS and CWNS. According to the Polyvagal Theory (Porges, 2009), children who demonstrate lower RSA at rest experience more vulnerability to emotional reactivity and less emotional regulation.…”
Section: Baseline Reactivity and Regulation In Cwsmentioning
confidence: 76%
See 3 more Smart Citations
“…However, our findings with the other autonomic nervous system measures (SCL and RSA) corroborate the existing psychophysiological studies of preschool-age CWS. Specifically, a recent study from our laboratory (Tumanova and Backes, 2019) and the studies of others (Jones et al, 2014;Zengin-Bolatkale et al, 2015) reported no significant differences in baseline SCL between preschool-age CWS and CWNS. According to the Polyvagal Theory (Porges, 2009), children who demonstrate lower RSA at rest experience more vulnerability to emotional reactivity and less emotional regulation.…”
Section: Baseline Reactivity and Regulation In Cwsmentioning
confidence: 76%
“…First, to establish a pre-experimental baseline for each participant's resting skin conductance level and heart rate, participants viewed an animated screensaver of a three-dimensional fish tank for four min. The screensaver contained minimal action and had been previously successfully used to establish baseline levels of electrodermal activity and heart rate in preschool-age children (e.g., Jones et al, 2014;Tumanova and Backes, 2019). Next, the participants completed two experimental conditions: (1) viewing pictures with negative valence, and (2) viewing pictures with neutral valence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While social anxiety is commonly reported in adults who stutter, the same has not been consistently reported in children who stutter. Direct examination of emotional processing in children who stutter has been rare, though some studies have reported subtle differences in CWS in terms of autonomic nervous system responses to challenging speech tasks (nonword repetition; (Tumanova & Backes, 2019)) or emotionally stressful stimuli ((Jones et al, 2014; Walsh et al, 2019). The current BBS results suggest that brain networks linked to emotional regulation and their connectivity with cognitive control networks may differentiate children who stutter.…”
Section: Discussionmentioning
confidence: 99%